A Critical Approach to Hartmut Rosa's Acceleration Theory - Duerto Porquet, Paula (Analysis. Journal of Philosophical Research, 2020)
This paper critically analyzes the main ideas of the theory of social acceleration exposed by Hartmut Rosa in Alienation and acceleration. The absence of an analysis of capitalism as a cause of acceleration is criticized. This absence also negatively affects the alternatives to alienation that Rosa proposes in Resonance.Key words: Hartmut Rosa, alienation, acceleration, resonance